A rapid and simple method of detection of Blepharisma japonicum using PCR and immobilisation on FTA paper - Hide, Geoff; Hughes, Jacqueline M.; McNuff, Robert (BMC Ecology, 2003)
The rapid expansion in the availability of genome and DNA sequence information has opened up new possibilities for the development of methods for detecting free-living protozoa in environmental samples. The protozoan Blepharisma japonicum was used to investigate a rapid and simple detection system based on polymerase chain reaction amplification (PCR) from organisms immobilised on FTA paper.